Retirement patterns during the Swedish pension reform - Glans, Erik (Uppsala, 2008)
"The Swedish pension reform of 1999-2003 provides an opportunity to study whether and how important economic incentives are for the timing of retirement. The new pension system provides a much closer link between contributions and benefits than the former system. I study whether the reform has led to delayed retirement by examining the retirement patterns of elderly Swedish workers that were differentially affected by the reform. I useduration analysis with annual data from the LINDA database. Discrete time proportional hazard models are estimated. The results show a remarkable decline in the retirement hazard among latter born cohorts, who were more affected by the reform. This implies that retirement is delayed. Most of the decline occurs among public sector employees."